Effect of vitamin D deficiency on the development of postoperative atrial fibrillation in coronary artery bypass patients - SÜNBÜL, MURAT (TABRIZ UNIV MEDICAL SCIENCES & HEALTH SERVICES, 2016)
Introduction: Various factors may be responsible for the development of postoperative atrial fibrillation (POAF) in coronary artery bypass graft (CABG) patients. In our study, we demonstrated the effect of vitamin D deficiency on the development of POAF. Methods: In this prospective case control study, patients undergoing elective, isolated CABG were considered. A total of 15 patients (16.6%) who developed POAF during the first five days after surgery made up the POAF group. Seventy-five patients that had a sinus rhythm in the same period were the non-POAF group. The two groups were compared statistically in terms of laboratory, clinical, echocardiographic, operative, and postoperative parameters. Results: All patients were in sinus rhythm at discharge. The baseline characteristics of the study groups were comparable. The POAF group had a lower vitamin D level than the non-POAF group (9.0 +/- 5.0 and 15.0 +/- 8.4 ng/mL, respectively; P = 0.007). In the POAF group, the patients' left atrium diameter and incidence of hypertension (HT) were higher than those of the non-POAF group. Conclusion: Incidence of POAF was significantly higher in patients with vitamin D deficiency or insufficiency than the patients with vitamin D level in normal range. Therefore vitamin D deficiency or insufficiency may be a predictor of POAF in patients with CABG.
Keywords: Vitamin D; Atrial Fibrillation; Coronary Artery Bypass Graft; CARDIAC-SURGERY; 1,25-DIHYDROXYVITAMIN D-3; GRAFT-SURGERY; RISK-FACTORS; FAILURE; INDEX